A practical guide to the diagnosis and management of osteoporosis in childhood and adolescence - Ward, Leanne M. (Frontiers in Endocrinology, 2024)
Osteoporosis in childhood distinguishes itself from adulthood in four important ways: 1. Challenges in distinguishing otherwise healthy children who have experienced fractures due to non-accidental injury or misfortunate during sports and play from those with an underlying bone fragility condition, 2. A preponderance of monogenic “early onset” osteoporotic conditions that unveil themselves during the pediatric years, 3. The unique potential, in those with residual growth and transient bone health threats, to reclaim bone density, structure and strength without bone-targeted therapy, and 4. The need to benchmark bone health metrics to constantly evolving “normal targets”, given the changes in bone size, shape and metabolism that take place from birth through late adolescence. On this background, the pediatric osteoporosis field has evolved considerably over the last few decades, giving rise to a deeper understanding about the discrete genes implicated in childhood-onset osteoporosis, the natural history of bone fragility in the chronic illness setting and associated risk factors, effective diagnostic and monitoring pathways in different disease contexts, the importance of timely identification of candidates for osteoporosis treatment, and the benefits of early (during growth) rather than late (post-epiphyseal fusion) treatment. While there has been considerable progress, a number of unmet needs remain, the most urgent of which is to move beyond the monotherapeutic anti-resorptive landscape to the study and application of anabolic agents that are anticipated to not only improve bone mineral density, but also increased cross-sectional bone diameter (periosteal circumference). The purpose of this review is to provide a practical guide to the diagnosis and management of osteoporosis in children presenting to clinic with fragility fractures, one that serves as a step-by-step “how to” reference for clinicians in their routine clinical journey. The article also provides a sightline to the future, emphasizing the clinical scenarios with the most urgent need for an expanded toolbox of effective osteoporosis agents in childhood.